Application of multivariate statistical analysis for delineation of prospective geochemical anomalies in Providenskaya Area (Chukotka, Russia) - Kirillova, M.; Yankovich, A.; Yankovich, E.; Maskov, A.; Chernyshov, Aleksey I.; Voroshilov, V. (IOP Conference Series: Earth and Environmental Science)
The secondary geochemical field structure was modelled on the basis of the lithogeochemical dispersion trains of the Providenskaya Area of the Chukotka Peninsula. The factor and cluster analysis were applied to interpret the nature of geochemical anomalies. It was proved that a range of anomalies were prospective for gold-silver, polymetallic, tin, and tungsten deposit allocation.